The human VRK1 chromatin kinase in cancer biology - Ignacio Campillo‐Marcos; Raúl García-González; Elena Navarro-Carrasco; Pedro A. Lazo (2021)
VRK1 is a nuclear Ser-Thr chromatin kinase that does not mutate in cancer, and is overexpressed in many types of tumors and associated with a poor prognosis. Chromatin VRK1 phosphorylates several transcription factors, including p53, histones and proteins implicated in DNA damage response pathways. In the context of cell proliferation, VRK1 regulates entry in cell cycle, chromatin condensation in G2/M, Golgi fragmentation, Cajal body dynamics and nuclear envelope assembly in mitosis. This kinase also controls the initial chromatin relaxation associated with histone acetylation, and the non-homologous-end joining (NHEJ) DNA repair pathway, which involves sequential steps such as γH2AX, NBS1 and 53BP1 foci formation, all phosphorylated by VRK1, in response to ionizing radiation or chemotherapy. In addition, VRK1 can be an alternative target for therapies based on synthetic lethality strategies. Therefore, VRK1 roles on proliferation have a pro-tumorigenic effect. Functions regulating chromatin stability and DNA damage responses have a protective anti-tumor role in normal cells, but in tumor cells can also facilitate resistance to genotoxic treatments.